2008
DOI: 10.1159/000117310
|View full text |Cite
|
Sign up to set email alerts
|

Circannual Rhythm of Laboratory Test Parameters among Chronic Haemodialysis Patients

Abstract: Background/Aims: Seasonal variations in laboratory test results have been pointed out in dialysis patients. Although the mechanism for this phenomenon is not clear, this could result in changes in dialysis and medication prescriptions. We investigated the effect of the circannual rhythm on laboratory test parameters in chronic haemodialysis patients. Methods: Data of 38 laboratory test parameters were collected every month and analyzed for 150 stable haemodialysis patients, with non-linear sine wave regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
22
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
9
22
2
Order By: Relevance
“…However, in other studies, no relationship between variations in extracellular volume and seasonal variations in BP was observed. 21 Of the laboratory parameters, serum potassium showed a seasonal variation with highest values in winter, in agreement with the results of Yanai et al (5), which might seem somewhat counterintuitive in view of a higher purposed fruit intake during summer (25). Although this might reflect a higher dietary intake in winter (1), phosphate levels were not significantly different between the various seasons in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in other studies, no relationship between variations in extracellular volume and seasonal variations in BP was observed. 21 Of the laboratory parameters, serum potassium showed a seasonal variation with highest values in winter, in agreement with the results of Yanai et al (5), which might seem somewhat counterintuitive in view of a higher purposed fruit intake during summer (25). Although this might reflect a higher dietary intake in winter (1), phosphate levels were not significantly different between the various seasons in our study.…”
Section: Discussionsupporting
confidence: 91%
“…No reliable data on phosphate binders were available in this study. In general, seasonal variations in laboratory parameters are not completely consistent between studies (3,5).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In other studies [12,13] blood pressure and overhydration showed the same synchronous circannual variations, with peaks in late autumn and early winter and troughs in summer. These biological variaIn this issue of Blood Purification, Yanai et al [1] provide the results on the circannual rhythm of laboratory test parameters among 150 chronic hemodialysis patients. The study was performed for 2 years to examine whether circannual variations in selected clinical and laboratory variables could be observed.…”
mentioning
confidence: 99%
“…In the study by Yanai et al [1] 38 laboratory parameters were measured either once or twice a month. The data clearly suggest a seasonal relationship between outside temperature and laboratory parameters, such as urea, potassium, phosphate, and total cholesterol, showing significantly higher levels in the winter as compared to the summer.…”
mentioning
confidence: 99%